Produção de pimentão em substratos e fertirrigação com efluente de biodigestor - Factor, Thiago L. [UNESP]; De Araújo, Jairo A. C. [UNESP]; Vilella Jr., Luiz V. E. [UNESP] (FapUNIFESP (SciELO), 2008)
The use of biological reactor effluent in fertigation and use of dry swine waste as a component of the substrate, would lower the cost of production and prevent discarding residues in the environment. Based on that, the objective of this research was to evaluate both yield and quality of pepper fruits, adopting the factorial scheme 4 x 3 in randomized blocks, with 4 substrates (S1, S2, S3 e S4) and 3 nutrient solutions: mineral nutrient solution (SN1), nutrient solution as based on biological reactor effluent boosted with mineral fertilizers (SN2) and nutrient solution based on biological reactor effluent (SN3). The different mixtures that yielded different substrate could be recommended for both fruit and quality production perspectives, except substrate 1 (S1), which revealed inferior quality of fruits. The use of SN1 permitted greater weight of the fruits, thickness of the pulp and productivity. Partial substitution of fertilizers by biodigestor effluent of swine waste (SN2) was not sufficient to promote productivity equivalent to 100% mineral nutrient solution, however it reached mean index of productivity with standards of quality of fruits equivalent to the mineral solution (SN1). This supports the conclusion that the use of the biological reactor effluent would be an alternative in potential to reduce the cost of production of pepper crop and to prevent the discarding of this material, still rich in nutrients, into the environment.
Pepper production in substrates using fertigation with biological reactor effluent
Keywords: Biofertilizer; Capsicum annuum L.; Soiless crop; Swine manure; Capsicum annuum; Suidae